The Effect of Intrinsic Defects on Resistive Switching Based on p–n Heterojunction - Zheng, K. (2015)
We report a unidirectional bipolar resistive switching in an n-type GaO x /p-type NiO x heterojunction fabricated by magnetron sputtering at room temperature. The resistive switching (RS) of the heterojunction directly relate with the concentration of intrinsic defects in oxide, such as oxygen vacancies and oxygen ions. Under external electric field, these electromigrated defects accumulate at the pn junction interface and modify the interface barrier, forming or rupturing the filamentary paths between n-GaO x and p-NiO x , leading to the switching between Ohmic and diode characteristics of the device.